PERANCANGAN KAPAL TANKER 17500 DWT KECEPATAN 12 KNOT UNTUK RUTE PELAYARAN BALIKPAPAN - SURABAYA - Tesalonika Deby, (2020)
Indonesia as a maritime country has a strategic position in the world shipping lane. This affects the need for ships is increasing, one of them is a tanker. Tankers have a high economic value. Because the refinery unit is quite far geographically, tanker has been evaluated as an efficient choice in terms of economic cost and effective distribution of oil. Tankers function to transport oil or its derivative products, not only from drilling to land, but also as a means of transporting oil trade between ports or between countries. Therefore, the author intends to design product oil tanker to distribute avtur 17500 DWT speed 12 knots for sea routes Balikpapan-Surabaya. The methods used in the design of this ship is comparation method, trial and error method, library research. The purpose of the comparison method is to compare between two different tanker data (comparator ships) with the reference to the difference being the DWT of each of the ships. While the trial method is an experimental method approach to the calculation with the control of finding errors and fixing them. To support the calculation process of ship design, a literary method is needed. This design has many steps, these are linesplan, general arrangement, hydrostatic analysis, bonjean curve, resistance analysis, ship propulsion, stability, and others.